Liquid crystal phase shifter for THz radiation with cholesteric liquid crystal. (2nd November 2017) - Chodorow, U.; Parka, J.; Strzezysz, O.; Mazur, R.; Morawiak, P.; Pałka, N.
ABSTRACT: In this work we present phase shifters with cholesteric liquid crystal (ChLC) for the terahertz (THz) range with fast modulation. The phase shift of presented phase shifters is equal ∼π at 2.5 THz. The characterization of the phase shifters was done by using terahertz time-domain spectroscopy from 0.3 THz up to 3 THz. Also electro-optical measurements were made to obtain response times of ChLC.